Controlled-Release and Slow-Release Fertilizers as Nutrient Management Tools - Guodong Liu; Lincoln Zotarelli; Yuncong Li; David Dinkins; Qingren Wang; Monica Ozores-Hampton (EDIS)
There are many fertilizer sources available for commercial crop production. The characteristics of each fertilizer type determine whether its use poses an advantage or a disadvantage to a farmer. This 7-page fact sheet focuses on how to select the right fertilizer to enhance profitability and satisfy best management practices (BMPs). Written by Guodong Liu, Lincoln Zotarelli, Yuncong Li, David Dinkins, Qingren Wang, and Monica Ozores-Hampton, and published by the UF Department of Horticultural Sciences, October 2014. (UF/IFAS Photo by Thomas Wright)